2004
DOI: 10.1111/j.1532-5415.2004.52054.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between a Dementia Diagnosis, Chronic Illness, Medicare Expenditures, and Hospital Use

Abstract: In a nationally representative sample, higher Medicare expenditures associated with a diagnosis of dementia are in large part due to increased hospitalization. Further study is needed into the factors associated with high rates of hospitalization in dementia patients including aspects of ambulatory management that may be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
370
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(397 citation statements)
references
References 32 publications
20
370
0
7
Order By: Relevance
“…Those who were obese or had been hospitalized in the past year were more likely to be cognitively impaired. These results were in line with other studies that found overweight women and obese men to have a higher likelihood of developing dementia (Elias et al, 2003;Gustafson et al, 2003), and dementia to be an important predictor of institutionalization (Bharucha et al, 2004;Bynum et al, 2004). In our study, short or long sleep was also found to be associated not only with cognitive impairment, but also depressive symptoms in elderly Japanese.…”
Section: Discussionsupporting
confidence: 82%
“…Those who were obese or had been hospitalized in the past year were more likely to be cognitively impaired. These results were in line with other studies that found overweight women and obese men to have a higher likelihood of developing dementia (Elias et al, 2003;Gustafson et al, 2003), and dementia to be an important predictor of institutionalization (Bharucha et al, 2004;Bynum et al, 2004). In our study, short or long sleep was also found to be associated not only with cognitive impairment, but also depressive symptoms in elderly Japanese.…”
Section: Discussionsupporting
confidence: 82%
“…[19][20][21][22][23] AHRQ-CCS disease categories have been widely used in numerous publications to identify comorbidities and outcomes, [24][25][26][27][28][29] predict mortality, 30,31 and estimate utilization and costs. [32][33][34][35] AHRQ-CCS disease categories are recognized by the Department of Defense Military Health System and are incorporated into Tricare data as an industry standard. 13 AHRQ-CCS category 49 (diabetes without complication) and category 50 (diabetes with complications) have been used in clinical research 36,37 and to generate reports on utilization and cost statistics in relation to diabetes and diabetic complications in various health care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment increases with aging. About 17 % of individuals with dementia reported association with COPD in the US Medicare database [66] and there is evidence that the occurrence of cognitive impairment is Fig. 1 Proposed factors influencing the choice of an inhaled corticosteroid (ICS) in elderly patients.…”
Section: Practical Considerations For Elderly Patients On Long-term Dmentioning
confidence: 99%